Perilaku Pencarian Informasi Mahasiswa Bidang Saintek dan Soshum Universitas Sam Ratulangi terhadap Jurnal Online - Nalole, Suci Ramadhani; Runtuwene, Anita; Rawis, Sintia Maria (Media Informasi, 2026)
This study explores the differences in information seeking behavior between students in science and technology (Saintek) and social sciences and humanities (Soshum) at Sam Ratulangi University in accessing online journals. Using a qualitative multiple case study design, data were collected through observation, interviews, and document analysis. Data analysis was conducted through the stages of individual case/informant analysis, cross-case/informant comparison, and cross-category analysis.The results show that Saintek students tend to follow a systematic and efficiency oriented pattern, while Soshum students demonstrate a more exploratory and reflective approach. These behavioral variations are influenced by academic culture, digital literacy, and learning orientation. The findings modify Meho and Tibbo’s information-seeking model into a more adaptive and contextual framework. This research provides empirical insights into how disciplinary differences shape students’ interaction with digital information and offers recommendations for university libraries to develop e-journal services aligned with users’ academic and cognitive characteristics.